Study and correlation of the severity of birth asphyxia with serum levels of glucose, uric acid and electrolytes in the cord blood of asphyxiated neonates - M. Y., Kavya; Rudrappa, Sudha; Gopal, Girish (International Journal of Contemporary Pediatrics, 2020)
Background: Perinatal asphyxia one of the most common primary cause of mortality and morbidity among neonates in India and is the commonest cause of stillbirths. Methods: This prospective study was conducted for a period of 18 months which included cases (124) and controls (124) comprised of asphyxiated and non-asphyxiated neonates respectively. The umbilical cord arterial blood was collected by double clamp technique and sent for analysis of electrolytes, uric acid and glucose. Results: Umbilical arterial sodium, calcium and glucose concentration was significantly lower in cases as compared to Control and potassium, uric acid and creatinine concentration was found to be on the higher in the cases as compared to the controls, and the difference was statistically significant with p<0.001. Conclusions: Metabolic abnormalities like hyponatremia, hypocalcaemia and hyperuricemia are significant risk factors for perinatal brain injury. Identification and treatment of such abnormalities results in improved outcome in affected neonates.